Inhibiting Polo-like kinase 1 causes growth reduction and apoptosis in pediatric acute lymphoblastic leukemia cells - Hartsink-Segers, Stefanie A. (Ferrata Storti Foundation, 2013)
This study investigated Polo-like kinase 1, a mitotic regulator often over-expressed in solid tumors and adult hematopoietic malignancies, as a potential new target in the treatment of pediatric acute lymphoblastic leukemia. Polo-like kinase 1 protein and Thr210 phosphorylation levels were higher in pediatric acute lymphoblastic leukemia (n=172) than in normal bone marrow mononuclear cells (n=10) (P<0.0001). High Polo-like kinase 1 protein phosphorylation, but not expression, was associated with a lower probability of event-free survival (P=0.042) and was a borderline significant prognostic factor (P=0.065) in a multivariate analysis including age and initial white blood cell count. Polo-like kinase 1 was necessary for leukemic cell survival, since short hairpin-mediated Polo-like kinase 1 knockdown in acute lymphoblastic leukemia cell lines inhibited cell proliferation by G2/M cell cycle arrest and induced apoptosis through caspase-3 and poly (ADP-ribose) polymerase cleavage. Primary patient cells with a high Polo-like kinase 1 protein expression were sensitive to the Polo-like kinase 1-specific inhibitor NMS-P937 in vitro, whereas cells with a low expression and normal bone marrow cells were resistant. This sensitivity was likely not caused by Polo-like kinase 1 mutations, since only one new mutation (Ser335Arg) was found by 454-sequencing of 38 pediatric acute lymphoblastic leukemia cases. This mutation did not affect Polo-like kinase 1 expression or NMS-P937 sensitivity. Together, these results indicate a pivotal role for Polo-like kinase 1 in pediatric acute lymphoblastic leukemia and show potential for Polo-like kinase 1-inhibiting drugs as an addition to current treatment strategies for cases expressing high Polo-like kinase 1 levels.